Marine Amphipods of the Macaronesian archipelagos and north-west African margin: checklist and geographical distribution - DAUVIN, JEAN-CLAUDE; BAKALEM, ALI; MENIOUI, MOHAMED (Mediterranean Marine Science, 2025)
An updated amphipod checklist for 2024 is given for the amphipods recorded from the adlittoralto abyssal zones of the Macaronesian archipelagos and the north-west African margin. Four marine regions are taken into account: 1) North West Africa (NWA), 2) Mauritania and Senegal (SEN), 3) Canary, Selvagens and Madeira Archipelagos (CAN MAD) and 4) the Cabo Verde Archipelago (CV). The total number of species recorded in these four regions is 509. CAN-MAD is the region with the greatest species richness (302 species), followed by NWA (297 species), SEN (152 species) and finally CV (122 species). Among the 509 species recorded, 66 have been described from this region while 59 are endemic. The most diverse family is the Ampeliscidae Krøyer, 1842 (32 species), the Scinidae Stebbing, 1888 (29 species), the Caprellidae Leach, 1814 (22 species). Then, five other families are each represented by 16 species or more, the Photidae Boeck, 1871, Maeridae Krapp-Schickel, 2008 and Ischryroceridae Stebbing, 1899 (17 species), Aoridae Stebbing, 1899 and Hyalidae Bulyčeva, 1957 (16 species). Only five species are non-indigenous or possibly non-indigenous. The biogeographical affinities of the benthic amphipods are highlighted by comparing them with communities from the continental/insular shelf of the four regions studied here as well as with three neighbouring areas, i.e.: part of the Lusitanian maritime province (BIS-IBE), the Mediterranean shores of Morocco and Algeria (MOR-ALG) and the Azores Archipelago (AZO). The CV and SEN fauna are distinguishable from the others, which form two main groups: the NWA, MORALG and BIS-IBE on the one hand, and the CAN-MAD and AZO archipelagos on the other. Future research should be focused along the coasts of Mauritania and Senegal and around the Cabo Verde Archipelago where there is a lack of knowledge not only on amphipods but also regarding marine invertebrate biodiversity in general. Special attention should be paid to biofouling in harbours since this is liable to increase the number of non-indigenous species which appears to be very low in the Macaronesian archipelagos in spite of the intense maritime traffic.